Review of Fundamentals of Covariant Quantum Mechanics in the Dual 4- Dimensional Space-Time : Substance of Wave Function, the Origin of Quantum Probability and the Cause of Quantum Superposition State (London Journal of Research In Science: Natural and Formal, 2023)
Microscopic objects have some spatial distribution, which influences quantum phenomena. The particle model does not apply to the microworld. In this work, we use a rotating field matter sphere model. The size of the sphere change along with the movement state, harmonized with special relativity. Thus, we independently construct a dual 4-dimensional space-time to describe the microscopic quantum phenomenon and established the objective reality of plural description, which has obvious theoretical advantages. In the dual 4-dimensional space-time, the wave function describes matter waves as physical waves. Which is the physical basis of quantum communication. Quantum probability originates from the tangible structure and matter density distribution of the microscopic objects and is reflected in the transformation of space-time. Matter waves and probability waves can be transformed by using Fourier transformation.
Keywords: field matter sphere; model; matter wave; quantum probability; origin; transformation of representation